Whole genome analysis of two sympatric human Mansonella: Mansonella perstans and Mansonella sp “DEUX” - Rodi, Miriam; Gross, Caspar; Sandri, Thaisa Lucas; Berner, Lilith; Marcet-Houben, Marina; Kocak, Ersoy; Pogoda, Michaela; Casadei, Nicolas; Köhler, Carsten; Kreidenweiss, Andrea; Agnandji, Selidji Todagbe; Gabaldón, Toni; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Mansonella species are filarial parasites that infect humans worldwide. Although these infections are common, knowledge of the pathology and diversity of the causative species is limited. Furthermore, the lack of sequencing data for Mansonella species, shows that their research is neglected. Apart from Mansonella perstans, a potential new species called Mansonella sp “DEUX” has been identified in Gabon, which is prevalent at high frequencies. We aimed to further determine if Mansonella sp “DEUX” is a genotype of M. perstans, or if these are two sympatric species. Methods We screened individuals in the area of Fougamou, Gabon for Mansonella mono-infections and generated de novo assemblies from the respective samples. For evolutionary analysis, a phylogenetic tree was reconstructed, and the differences and divergence times are presented. In addition, mitogenomes were generated and phylogenies based on 12S rDNA and cox1 were created. Results We successfully generated whole genomes for M. perstans and Mansonella sp “DEUX”. Phylogenetic analysis based on annotated protein sequences, support the hypothesis of two distinct species. The inferred evolutionary analysis suggested, that M. perstans and Mansonella sp “DEUX” separated around 778,000 years ago. Analysis based on mitochondrial marker genes support our hypothesis of two sympatric human Mansonella species. Discussion The results presented indicate that Mansonella sp “DEUX” is a new Mansonella species. These findings reflect the neglect of this research topic. And the availability of whole genome data will allow further investigations of these species